A transformative solution to build effective, transparent, and resilient "fit-for-purpose" national health research ethics systems - Manju Rani; Neha Chawla; Nitya Wadhwa; Roli Mathur; Timothy Jinks; Priyanka Das; Suman Rijal (BMC, 2024)
Abstract The current research ethics review systems are composed of isolated institutional Research Ethics Committees (RECs) that develop their own standard operating procedures (SOPs), templates and so on, with low adoption of digital solutions to manage submission and review processes. This poses several challenges, such as delays, higher costs, and hindering multi-site research. We propose an online national research ethics platform that all RECs can use, with common review processes and documentation requirements following national policy. The system will scale up adoption of digital solutions to all RECs. It will reduce administrative burden and harmonize review procedures. It will also obviate the need for separate and isolated interventions such as national REC registries or clinical trial registries, as these can be generated as transactional outputs of the system. The harmonized procedures and possibility of single submission will facilitate multi-site research. Sharing of resources and expertise among RECs on the platform will enhance resilience. An e-EC system developed in India and a Regional Health research portal developed by the WHO South-East Asia office offer proof of concepts to demonstrate the feasibility of developing and using such systems. The proposed solution is ambitious but feasible. Developing the proposed system will be a vital cost-effective investment in national health infrastructure to strengthen the research ecosystem and accelerate delivery of improved healthcare innovations by reducing unnecessary delays in conducting research. To maximize benefits, concurrent efforts are needed to build researchers' capacity and enhance the quality and efficiency of human reviews of the research proposals by REC.